Evaluation of fluralaner and afoxolaner treatments to control flea populations, reduce pruritus and minimize dermatologic lesions in naturally infested dogs in private residences in west central Florida USA - Dryden, Michael W.; Canfield, M. S.; Kalosy, Kimberly; Smith, Amber; Crevoiserat, Lisa; McGrady, Jennifer C.; Foley, Kaitlin M.; Green, K.; Tebaldi, C.; Smith, Victorene E.; Bennett, Tashina; Heaney, K.; et al. (My University, 2016)
Background: A study was conducted to evaluate and compare the effectiveness of two different oral flea and tick products to control flea infestations, reduce pruritus and minimize dermatologic lesions over a 12 week period on naturally infested dogs in west central FL USA. Methods: Thirty-four dogs with natural flea infestations living in 17 homes were treated once with a fluralaner chew on study day 0. Another 27 dogs living in 17 different homes were treated orally with an afoxolaner chewable on day 0, once between days 28-30 and once again between days 54-60. All products were administered according to label directions by study investigators. Flea populations on pets were assessed using visual area counts and premise flea infestations were assessed using intermittent-light flea traps on days 0, 7, 14, 21, and once between days 28-30, 40-45, 54-60 and 82-86. Dermatologic assessments were conducted on day 0 and once monthly. Pruritus assessments were conducted by owners throughout the study. No concurrent treatments for existing skin disease (antibiotics, anti-inflammatories, anti-fungals) were allowed. Results: Following the first administration of fluralaner or afoxolaner, flea populations on pets were reduced by 99.0 % and 99.3 %, respectively within 7 days. Flea populations on the fluralaner treated dogs were 0 (100 % efficacy) on days 54-60 and 82-86 after the administration of a single dose on day 0. Administration of 3 monthly doses of afoxolaner reduced flea populations by 100 % on days 82-86. Flea numbers in indoor-premises were markedly reduced in both treatment groups by days 82-86, with 100 % and 98.9 % reductions in flea trap counts in the fluralaner and afoxolaner treatment groups, respectively. Marked improvement was observed in FAD lesion scoring, Atopic Dermatitis lesions scoring (CADESI-4) and pruritus scores with both formulations. Conclusions: In a clinical field investigation conducted during the summer of 2015 in subtropical Florida, a single administration of an oral fluralaner chew completely eliminated dog and premises flea infestations and markedly reduced dermatology lesions and pruritus. Three monthly doses of the afoxolaner chewable also eliminated flea infestations in dogs, markedly reduced premises' flea populations and similarly improved dermatology lesions and pruritus.
Citation: Dryden, M. W., Canfield, M. S., Kalosy, K., Smith, A., Crevoiserat, L., McGrady, J. C., . . . Sun, F. (2016). Evaluation of fluralaner and afoxolaner treatments to control flea populations, reduce pruritus and minimize dermatologic lesions in naturally infested dogs in private residences in west central Florida USA. Parasites & Vectors, 9, 11. doi:10.1186/s13071-016-1654-7
Keywords: Ctenocephalides Felis Felis; Cat Flea; Dogs; Field Study; Fluralaner; Flea